'Last goal wins': re/engaging women of a 'forgotten' age through football?. Issue 7 (2nd September 2019) - Stride, Annette; Drury, Scarlett; Fitzgerald, Hayley
ABSTRACT: This paper explores the physical activity experiences of a group of women based in England, and who are over the age of 30. This particular age group represent a 'forgotten' age, that is, they are largely ignored in academic scholarship, policy and physical activity provision. The paper explores how this group of women 're/engaged' in physical activity after a sustained period of inactivity. The study is situated in a weekly football initiative (Monday Night Footy) based in the north of England, managed and organised by a group of women for women to train and play five-a-side football. Data were generated through semi-structured interviews and the use of photo-biographical boards with 11 women, all of whom are regular participants to the football sessions. We use a middle ground feminist lens and Archer's notion of 'fr/agility' to help make sense of the women's experiences. From these women's stories three key findings emerge: (a) Biographies of (in)activity – the ways in which relationships with physical activity can be characterised by fractures and fissures despite seemingly positive early physical activity experiences; (b) Pathways of re/engagement – the motives and enablers to these women once again participating in physical activity after a sustained absence; and (c) Monday Night Footy as a space for re/engagement – the ways in which this context contributes to these women's continued involvement in football and broader physical activity. The paper concludes by offering policy makers and physical activity providers with some recommendations alongside considerations for future research.